Empowering African-Canadian Career Excellence - Community Economic Development and Employability Corporation (CEDEC) (2019)
The African-Canadian Career Excellence (ACCE) initiative was developed to address the loss of highly-educated, English-speaking Black youth from the Greater Montreal Area (Quebec, Canada) facing issues of unemployment and underemployment.
Keywords: Official Language Minority Community (OLMC)

Brief to Appele Quebec on Bill 40 : an Act to Amend Mainly the Education Act with Regard to School Organization and Governance - Buck, John (Community Economic Development and Employability Corporation (CEDEC), 2019)
The Community Economic Development and Employability Corporation, CEDEC, has been intimately involved over the last twenty-five years in developing and enhancing the vitality of the English-speaking Minority Community of Quebec. CEDEC is committed to improving the economic well-being of communities. It is a hub of innovative research and practice focused on enhancing economic activity that benefits communities through public, private, and civil society collaboration.

English-Speaking Quebecers : Views on Governance - Quebec Community Groups Network (QCGN); Community Economic Development and Employability Corporation (CEDEC); Quebec English School Boards Association (QESBA); Association for Canadian Studies (ACS) (2019)
Keywords: Official Language Minority Community (OLMC)

English-Speaking Quebecers: Views on School Boards - Quebec Community Groups Network (QCGN); Community Economic Development and Employability Corporation (CEDEC); Quebec English School Boards Association (QESBA); Association for Canadian Studies (ACS) (2019)
Keywords: Official Language Minority Community (OLMC)

Guide à l'intention du récolteur : Pour le démarrage d'une entreprise de réolte de matières premières naturelles sur la Basse-Côte-Nord (QC) - Poole, Jessica (2019)

Harvester's Guide : Starting a Raw Materials Harvesting Business : Lower North Shore, QC - Poole, Jessica (2019)

Tourism 2025 : CEDEC's Plan for Creating 46,900 Jobs and Adding $5.2 Billion to the Economy - Community Economic Development and Employability Corporation (CEDEC) (2017)

Tourisme 2025 : Le plan de la CEDEC pour cré2r 46 9000 emplois et ajouter 5.2 milliards de dollar à l'économie - Community Economic Development and Employability Corporation (CEDEC) (2017)

African-Canadian Career Excellence : 2015 Employer Survey - Community Economic Development and Employability Corporation (CEDEC) (2015)
This report provides the final data analysis and interpretation of the 2015 employer survey on the hiring norms and practices of businesses across various sectors and industries in the Greater Montreal area, with a focus on employers’ attitudes towards the importance of a having a diverse workforce. This study is part of the African-Canadian Career Excellence (ACCE) initiative aimed at countering the migration of Black graduates from Montreal.

African-Canadian Career Excellence : 2014 Student Survey : The Needs and Challenges of Education Black Youth in Obtaining Meaningful and Sustainable Employment - Community Economic Development and Employability Corporation (CEDEC) (2015)

Initiative pour l'excellence de la carrière des Afro-Canadiens : Enquête réalisée en 2014 : Les besoins et les défis auxquels font face les jeunes de race noire pour obtenir un emploi rémunérateur et durable - Community Economic Development and Employability Corporation (CEDEC) (2015)
Ce rapport présente l’analyse et l’interprétation de l’enquête réalisée auprès des étudiants du premier cycle universitaire en 2014 sur leurs perceptions de la transition vers l’emploi à Montréal. Ce résumé, une étape réalisée par l’Initiative pour l’Excellence de la carrière des Afro-Canadiens œuvrant à contrer la migration des jeunes diplômés noir montréalais, vise à influencer la conception de formations s’adressant aux jeunes diplômés afin de faciliter le lancement de leur carrière et la progression de celle-ci au Québec.

Îles-de-la-Madeleine : Portrait de la communauté d'expression anglaise - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
Le présent portrait a été réalisé en collaboration avec de nombreux partenaires locaux, à l’initiative du Conseil des anglophones madelinots (CAMI) et avec l’appui du Réseau communautaire de santé et de services sociaux (RCSSS). Parmi les autres groupes ayant participé au processus figurent la Municipalité de Grosse-Île, l’école de Grosse-Île, la Corporation d’employabilité et de développement économique communautaire (CEDEC), le Centre scolaire communautaire (CSC) et l’Agglomération des Îles (comité de développement social/Les Îles en Forme).

Portrait of the English-speaking Community of the Magdalen Islands - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This portrait has been completed in collaboration with many local partners, through the initiative of the Council for Anglophone Magdalen Islanders (CAMI), with support from the Community Health and Social Services Network (CHSSN). Other groups involved in this process include the municipality of Grosse-Ile, the Grosse-Ile school, the Community Economic Development and Employability Corporation (CEDEC), the Community Learning Centre (CLC), Agglomération des Îles (social development committee/Les Îles en Forme).

Le Canada, le bilinguisme et le commerce - Arcand, Alan; Le Conference Board du Canada (Community Economic Development and Employment Corporation (CEDEC), 2013)
Le français est l’une des principales langues mondiales. Selon l’Organisation internationale de la francophonie (OIF), au moins 220 millions de personnes le parlent dans le monde1. C’est la langue officielle de tous les organismes des Nations unies et d’un grand nombre d’organisations internationales. Le français a pris naissance en France et s’est répandu grâce à l’expansion de ce pays outre-mer. Actuellement, quelque 30 pays dans le monde, dont le Canada, comptent le français parmi leurs langues officielles.

Canada, Bilingualism and Trade - Arcand, Alan; The Conference Board of Canada (Community Economic Development and Employment Corporation (CEDEC), 2013)
The French language is one of the world’s major languages. According to L’Organisation internationale de la Francophonie (OIF), at least 220 million people in the world speak French. It’s the official language of all United Nations agencies and a large number of international organizations. The language originated in France and spread by way of the country’s overseas expansion. Today, some 30 countries in the world, including Canada, have recognized French as an official language.

Canada, Bilingualism and Trade - Arcand, Alan; The Conference Board of Canada (Community Economic Development and Employment Corporation (CEDEC), 2013)
The French language is one of the world’s major languages. According to L’Organisation internationale de la Francophonie (OIF), at least 220 million people in the world speak French. It’s the official language of all United Nations agencies and a large number of international organizations. The language originated in France and spread by way of the country’s overseas expansion. Today, some 30 countries in the world, including Canada, have recognized French as an official language.

African-Canadian Career Excellence : Undergraduate Survey 2011-2012 Summary Report - Community Economic Development and Employability Corporation (CEDEC) (2013)
This summary report provides the final data analysis and interpretation of the 2011-2012 undergraduate student survey on perceptions of transition to employment in Montreal. As one step in the African-Canadian Career Excellence (ACCE) initiative aimed at countering the migration of Black graduates from Montreal, this summary will inform the design of development training for young graduates to facilitate their career launch and advancement in Quebec. Information and insights herein were provided by the following members of ACCE: Dorothy W. Williams of the Black Community Resource Centre (BCRC), Dwight Best of the African and Caribbean Students’ Network of Canada (ACSioN), Tamara Hart of the Tyndale St-Georges Community Centre, Velda Bourne, Karima West, and Nina Kim and Larissa Milo-Dale of the Community Economic Development and Employability Corporation (CEDEC). Preliminary data analysis and interpretation were contributed by Jan Warnke J W COMM INC.

Initiative pour l'excellence de la carrière des Afro-Canadiens : Sondage réalisé auprès des étudiants du premier cycle universitaire - Community Economic Development and Employability Corporation (CEDEC) (2013)
Ce rapport sommaire consigne les résultats et l'interprétation de l'analyse des données du sondage réalisé auprès des étudiants au premier cycle universitaire de 2011-2012 sur leurs perceptions de la transition vers le marché du travail de Montréal. Comme l’une des démarches de l'Initiative pour l’Excellence de la carrière des Afro-Canadiens consiste à contrer la migration des diplômés noirs de Montréal, ce rapport influencera l'élaboration de formations de perfectionnement pour les jeunes diplômés afin de faciliter l’amorce de leur carrière et leur progression professionnelle au Québec.

Business Vitality Initiative : Community Handbook - Community Economic Development and Employability Corporation (CEDEC) (2010)
If you’re not asking these questions, it’s unlikely you’re maximizing the potential of your community. Communities identifying their strengths, their gaps and their unexplored opportunities— that is what’s behind the BVI, a measurement and action process that helps communities harness their business potential. It has been designed to help communities assess their capacity to work with and support entrepreneurs, and to foster business growth. The BVI has been employed in communities across Canada (and recently in Australia) by a team based in Nelson, BC. The CIEL/BVI Team has been nominated for BC’s top award in community economic development and most recently won an award as the region’s most innovative organization. The BVI measures the perceptions of community leaders, business people and citizens about the current business environment in the community and compares the scores to those from other communities using a unique graphical index (the Business Vitality Index).

Business Vitality Initiative : Facilitator Handbook - Community Economic Development and Employability Corporation (CEDEC) (2010)
The Purpose of this Manual: The BVI includes two highly structured public meetings which require expert facilitation. This manual is a basic resource for facilitators. Other necessary resources include: • The BVI PowerPoint presentation • The BVI Community Handbook • Discussions with CIEL management • Discussions with the Community Sponsor • A BVI Assessment Report and Final Report from another community

Business vitality initiative : Manuel de l'animateur - Community Economic Development and Employability Corporation (CEDEC) (2010)
Le Business Vitality Initiative (BVI) comprend deux assemblées publiques très structurées qui doivent être animées par un expert. Le Manuel est la ressource principale des animateurs de ces assemblées, mais d’autres ressources sont aussi mises à leur disposition, notamment : • le diaporama sur le BVI; • le Manuel de la communauté – BVI; • le compte rendu des discussions avec la direction du CIEL; • le compte rendu des discussions avec l’organisme de parrainage communautaire; • un rapport d’évaluation dans le cadre du BVI et le rapport définitif d’une autre communauté.